Preparation, characterization, and in vivo pharmacokinetics of thermosensitive in situ nasal gel of donepezil hydrochloride - Gu Fugen; Fan Huimin; Cong Zhixin; Li Shuang; Wang Yi; Wu Chunzhi (Acta Pharmaceutica)
Donepezil hydrochloride thermosensitive in situ gel for nasal delivery was prepared by using Poloxamer 407 and Poloxamer 188 as thermoreversible polymers, hydroxypropyl-β-cyclodextrin and ethylparaben as permeation enhancer and preservative, respectively. The gelation temperature and time, pH value of the gel formulation were found to meet the requirements for nasal administration. The in vitro erosion and in vitro release tests exhibited obvious drug sustained release behavior. Meantime, main pharmacokinetic parameters such as tmax, cmax and AUC in plasma as well as in brain were significantly different between the nasal gel formulation and intragastric drug solution in rats (p < 0.01). The relative bioavailability and drug targeting efficiency of the gel formulation were calculated to be 385.6 and 151.2 %, respectively. Thus, the drug gel formulation might be a potential new delivery system for treatment of Alzheimer’s disease due to its higher bioavailability and better distribution to brain when compared to oral route.